First integrated implosion experiments on the SG-III laser facility. (2nd July 2018) - Pu, Yudong; Huang, Tianxuan; Ge, Fengjun; Zou, Shiyang; Wang, Feng; Yang, Jiamin; Jiang, Shaoen; Ding, Yongkun
Abstract: We present the first integrated implosion experiments which were carried out on the SG-III Laser facility in 2015. Vacuum hohlraums and squared laser pulses were used in the experiments. The purpose of the experiments was to demonstrate the one-dimensional implosion performance at low-convergence ratios. To characterize the implosion performance, the hohlraum energetics, the implosion dynamics and the nuclear products were measured. In particular, the radiation flux was diagnosed through laser entrance hole at different angles by an array of flat response detectors, and the energy and the spectrum of the back-scattered lasers were monitored for 8 laser beams which correspond to 2 beams in each cone at the lower hemisphere. Moreover, the hotspot shape was imaged using KB microscopes of high spatial resolution simultaneously from the equator and polar views. Taking advantage of the high resolution, some detailed structures in the hotspots were noticed. For the best implosion performances, the neutron yields over 1D calculation reached 50% at the convergence-ratios of 15.